2016
DOI: 10.1109/taes.2016.150712
|View full text |Cite
|
Sign up to set email alerts
|

Robust SAR STAP via Kronecker decomposition

Abstract: Abstract-This paper proposes a spatio-temporal decomposition for the detection of moving targets in multiantenna SAR. As a high resolution radar imaging modality, SAR detects and localizes non-moving targets accurately, giving it an advantage over lower resolution GMTI radars. Moving target detection is more challenging due to target smearing and masking by clutter. Space-time adaptive processing (STAP) is often used to remove the stationary clutter and enhance the moving targets. In this work, it is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…However, they usually assume complex Gaussian distributed samples. Then, the structured CM estimation is addressed either by projecting the Sample Covariance Matrix onto a subset describing a structure [9,10] or by deriving the Maximum Likelihood (ML) estimator under structure constraints. In some practical applications, performance is degraded because the assumption of Gaussian distribution leads to nonrobustness, either to heavy-tailed distributed data or to outliers in the sample set.…”
Section: Introductionmentioning
confidence: 99%
“…However, they usually assume complex Gaussian distributed samples. Then, the structured CM estimation is addressed either by projecting the Sample Covariance Matrix onto a subset describing a structure [9,10] or by deriving the Maximum Likelihood (ML) estimator under structure constraints. In some practical applications, performance is degraded because the assumption of Gaussian distribution leads to nonrobustness, either to heavy-tailed distributed data or to outliers in the sample set.…”
Section: Introductionmentioning
confidence: 99%
“…3 While in SAR GMTI B is not exactly low rank, it is approximately low rank in the sense that significant energy concentration in a few principal components is observed over small regions. 1,31 Due to the long integration time and high cross range resolution associated with SAR, the returns from the general class of moving targets are more complicated, making simple Doppler filtering difficult. During short intervals for which targets have constant Doppler shift f (proportional to the target radial velocity) within a range bin, the return has the form…”
Section: Sirv Clutter Modelmentioning
confidence: 99%
“…Space-time adaptive processing (STAP) is often used on multiantenna SAR to remove the stationary clutter and enhance the moving targets. In (Greenewald et al, 2016), 1 it was shown that the performance of STAP can be improved by modeling the clutter covariance as a space vs. time Kronecker product with low rank factors, providing robustness and reducing the number of training samples required. In this work, we present a massively parallel algorithm for implementing Kronecker product STAP, enabling application to very large SAR datasets (such as the 2006 Gotcha data collection) using GPUs.…”
mentioning
confidence: 99%
“…In general, current multi‐channel SAR moving target detection (MTD) techniques can be classified, based on whether a clutter cancellation or suppression step is applied prior to the detection, into two classes. The first one includes MTD approaches applying a clutter cancellation step before detection, such as space‐time adaptive processing (STAP) [2–4] and displaced phase centre antenna (DPCA) [5, 6]. STAP is a two‐dimensional (2D) adaptive filtering algorithm that suppresses the clutter by placing nulls in their directions of arrival and Doppler frequencies while maintaining a constant output of moving target contained in the tested signal [2].…”
Section: Introductionmentioning
confidence: 99%